Pengaruh Permainan Tradisional Hadang Rintang Berbasis Socratic Method Terhadap Peningkatan Kemampuan Character Strength Justice - Rinda Tri Juniarti (COLLASE (Creative of Learning Students Elementary Education), 2022)
AbstractCharacter Strength Justice is a social force that underlies positive social life. There are 3 indicators of success in Character Strength Justice, namely Citizenship (membership), Fairnes (fairness and equality), Leadership (leadership). The 3 success indicators are used as a reference to see the character strength justice possessed by students, through the socratic method-based obstacle course game. The purpose of this study was to identify the effect of the traditional game of Hadang Rintang based on the socratic method to see the improvement of the character strength justice abilities of elementary school students. This study uses the Pre-Experimental method with one group pretest-posttest design). The sample of this research was determined by non-probability sampling and using purposive sampling technique (purposed sample), namely class V SDN 1 Kalangsari as many as 25 students. The instrument of this research is a questionnaire to measure character strength justice. The results showed that there was an effect of traditional games based on the socratic method on increasing students' character strength justice abilities.Key Word: Traditional game of obstacles, Socratic Method, Character Strength Justice.AbstrakCharacter Strength Justice merupakan kekuatan social yang melandasi kehidupan bermasyarakat secara positif. Terdapat 3 indikator keberhasilan dalam Character Strength Justice yakni Citizenship (keanggotaan), Fairnes (keadilan dan persamaan), Leadership (kepemimpinan). Didalam 3 indkiator keberhasilan tersebut dijadikan acuan untuk melihat Character Strength Justice yang dimiliki siswa, melalui permainan hadang rintang berbasis socratic method. Tujuan dari penelitian ini adalah untuk mengidentifikasi pengaruh permaianan tradisional hadang rintang berbasis socratic method untuk melihat peningkatan kemampuan Character Strength Justice siswa sekolahh dasar. Penelitian ini menggunakan metode Pre-Eksperimental dengan desain one group pretest-posttest design). Sampel penelitian ini ditentukan secara nonprobability sampling dan menggunakan teknik purposive sampling (sampel bertujuan) yaitu kelas V SDN 1 Kalangsari sebanyak 25 siswa. Instrument penelitian ini berupa angket untuk mengukur Character Strength Justice. Hasil penelitian menunjukan bahwa terdapat pengaruh permainan tradisional berbasis socratic method terhadap peningkatan kemampuan Character Strength Justice siswa.Kata Kunci: Permainan tradisional hadang rintang, Socratic Method, Character Strength Justice.